Gluconacetobacter diazotrophicus PAL5 possesses an active quorum sensing regulatory system - Bertini, Elisa Violeta (2014)
The endophytic bacterium Gluconacetobacter diazotrophicus colonizes a broad range of host plants. Its plant growth-promoting capability is related to the capacity to perform biological nitrogen fixation, the biosynthesis of siderophores, antimicrobial substances and the solubilization of mineral nutrients. Colonization of and survival in these endophytic niche requires a complex regulatory network. Among these, quorum sensing systems (QS) are signaling mechanisms involved in the control of several genes related to microbial interactions, host colonization and stress survival. G. diazotrophicus PAL5 possesses a QS composed of a luxR and a luxI homolog, and produces eight molecules from the AHL family as QS signals. In this report data are provided showing that glucose concentration modifies the relative levels of these signal molecules. The activity of G. diazotrophicus PAL5 QS is also altered in presence of other carbon sources and under saline stress conditions. Inactivation of the QS system of G. diazotrophicus PAL5 by means of a quorum quenching strategy allowed the identification of extracellular and intracellular proteins under the control of this regulatory mechanism.